Demonstration Of Supplementary Food Preparation Using Tempe and Moringa Pudding - Octaviani, Rizki Eka Sakti; Anggraini, Dhian Fitri; Mawardani. T, Dinaryati (UKInstitute, 2026)
Nutritional problems are still the main health issue in Indonesia, including in Labibia Village, Mandonga District, Kendari City. Cases of Chronic Energy Deficiency (KEK) in pregnant women and toddlers T in toddlers show the need for community-based nutrition interventions. One of the efforts made is through a demonstration of making Supplementary Feeding (PMT) made from local ingredients